Flavonoid compound of Cucurbita moschata at three different altitudes - SURANTO SURANTO; NUR RAHMAH HIDAYATI; MUHAMMAD FURQAN; EDWI MAHADJOENO; SAJIDAN SAJIDAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suranto, Hidayati NR, Furqan M, Mahadjoeno E, Sajidan. 2023. Flavonoid compound of Cucurbita moschata at three different altitudes. Biodiversitas 24: 1853-1860. The aims of this research were to examine the presence of flavonoids, both the total and the content of quercetin and kaempferol, in Cucurbita moschata (Duchesne) Duchesne ex Poir. leaf growing at different altitudes. First, Thin Layer Chromatography (TLC) was used to detect the presence of flavonoid substances, followed by the colorimetric AlCl3 method to look at the Total Flavonoid Content (TFC). Finally, one-way ANOVA was employed to analyze quantitatively. Accordingly, High-Performance Liquid Chromatography (HPLC) method was used to test whether any member of flavonoid substances was found. The results showed that flavonoid substances of C. moschata leaf samples were detected, and the Rf value of every single altitude was not significantly different. However, the highest total flavonoid content was recorded from the middle altitude (1.369 mg QE/g); the lowest was found in the highest (0.244 QE/g). Furthermore, HPLC tests showed that retention times of quercetin at every single altitude from the lowest to the highest one were not much different. Meanwhile, kaempferol's retention time was recorded at 13.001 minutes for the lowest altitude and 12.955 and 12.965 minutes for the middle and highest altitudes, respectively. These preliminary results, especially the total flavonoid content in different altitudes, could detect various flavonoid members, such as quercetin and kaempferol, for the next project.